Analysis Of Entrepreneurial Spirit on The Success of Broiler Plasma Farmer in Gianyar District, Bali Province - I Gusti Agus Maha Putra Sanjaya; I Dewa Nyoman Sudita; Ni Ketut Etty Suwitari (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
The increase in the population of broiler chickens is in line with the increasing public demand for chicken and the improving economy of Bali in the new normal period of Covid-19. The entrepreneurial spirit plays an important role in the progress of the broiler business. This study aims to analyze: 1) the level of entrepreneurial spirit of farmers, 2) which indicators of the entrepreneurial spirit and characteristics of farmers have the most dominant influence on the success of broiler business, and 3) the influence of entrepreneurial spirit and farmer's characteristics on the success of broiler business in Gianyar Regency, Bali Province. The study was conducted using a purposive sampling method. Simple random sampling was conducted on 40 farmers using a structured questionnaire to obtain primary research data. Data were analyzed using Partial Least Square (PLS). The results showed that most respondents had a high entrepreneurial spirit. The entrepreneurial spirit of breeders is proven to be influenced by self-confidence, initiative, has an achievement motive, a leadership spirit, and likes, where liking challenges is the strongest indicator to reflect this variable. While age, education, skills, number of chicken ownership, and knowledge influence the individual characteristics of breeders. The number of chicken owners is the most dominant reflecting indicator.